Application of Article 6(1) of the ECHR in Civil Proceedings: The Effect of European Integration Processes on Ukrainian Legislation - Bobryk, Volodymyr; Bilianska, Nataliia; Petrovskyi, Andrii; Mazur, Viktoriia; Zaporozhchenko, Arkadii (European Journal of Sustainable Development, 2025)
The aim of the research is to consider the specifics of application of Article 6(1) of the ECHR, as well as to examine the way national courts use it when administrating justice in civil proceedings as part of euro-integration obligations by our State. Methodology. The methods applied in the article are: historical; hermeneutic; structural and functional; system and structural; formal and logical; case study method. Findings. The development of the institution of judicial protection of person’s rights in Ukrainian legislation, its system, as well as the institutionalization of international guarantees for human rights and freedoms are traced. The key principles of Article 6 of the Convention, which are also fundamental elements of the right to a fair trial are studied in detail. The relevant ECHR practice, as well as the decisions by the Supreme Court of Ukraine that are grounded on applying this rule of the Convention, are examined. Practical implications. It is summarized that national courts need to meticulously and comprehensively establish and investigate all the facts of each dispute and objectively assess the conformity of the application of legal rules. It is also advisably to carefully study the current ECHR case-law, as it is dynamically developing and may differ from previous positions. Keywords: European Convention on Human Rights (ECHR; Convention), European Court on Human Rights (ECtHR; the Court), Supreme Court of Ukraine (SCU), ECtHR case-law, protecting individual’s rights and freedoms, Article 6(1).